2018
DOI: 10.1002/ijc.31220
|View full text |Cite
|
Sign up to set email alerts
|

Palbociclib synergizes with BRAF and MEK inhibitors in treatment naïve melanoma but not after the development of BRAF inhibitor resistance

Abstract: Increased CDK4 activity occurs in the majority of melanomas and CDK4/6 inhibitors in combination with BRAF and MEK inhibitors are currently in clinical trials for the treatment of melanoma. We hypothesize that the timing of the addition of CDK4/6 inhibitors to the current BRAF and MEK inhibitor regime will impact on the efficacy of this triplet drug combination. The efficacy of BRAF, MEK and CDK4/6 inhibitors as single agents and in combination was assessed in human BRAF mutant cell lines that were treatment n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 53 publications
(126 reference statements)
1
40
0
Order By: Relevance
“…One such change is upregulation of the cell cycle genes CDK6 and CCND1 [ 89 ]. This appears to open up the possibility of using CDK inhibitors to overcome resistance; preclinical data indicate that adding palbociclib to treatment with BRAF inhibitors and/or MEK inhibitors prevented resistance development in treatment-naïve melanoma cells and animal models, but did not overcome resistance in cells and animals with acquired BRAF inhibitor resistance [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…One such change is upregulation of the cell cycle genes CDK6 and CCND1 [ 89 ]. This appears to open up the possibility of using CDK inhibitors to overcome resistance; preclinical data indicate that adding palbociclib to treatment with BRAF inhibitors and/or MEK inhibitors prevented resistance development in treatment-naïve melanoma cells and animal models, but did not overcome resistance in cells and animals with acquired BRAF inhibitor resistance [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our data also provide rationale for using CDK4/6 inhibitors in combination with BRAF or MEK inhibitors, as the number of cells driven into an ERK low quiescent-like by Dabrafenib or Binimetinib in combination with Palbociclib was greater than following treatment by any single agent. Indeed, such combinations have proven effective in KRAS mutant melanoma, colorectal cancer and Non-small cell lung cancer (94,95,96,97,98).…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining long-term response is difficult, with just 20% of patients in one study remaining progression free [234]. Ongoing research is investigating the addition of CDK, MAPK, or immune checkpoint inhibitors to combat resistance [231,235,236]. Recently, Misek et al identified RhoA GTPases as a potential pathway for BRAF resistance and that inhibition of the pathway by Rho kinase (ROCK) inhibitors promotes resensitization to BRAF-targeting therapy [237].…”
Section: B-rafmentioning
confidence: 99%